2017
DOI: 10.1002/celc.201700640
|View full text |Cite
|
Sign up to set email alerts
|

Facile Solvothermal Synthesis of Pt4Co Multi‐dendrites: An Effective Electrocatalyst for Oxygen Reduction and Glycerol Oxidation

Abstract: In this work, hierarchical Pt4Co multi‐dendrites (MDs) with abundant active sites were synthesized by using a one‐pot solvothermal co‐reduction approach, where cetyltrimethylammonium chloride (CTAC), citric acid, and oleylamine served as the structure director, eco‐friendly reducing agent, and co‐reductant, respectively. The architectures were mainly characterized by using a series of characterization techniques, demonstrating the enlarged electrochemically active surface area of 28.27 m2 g−1, much enhanced ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…Although the Pt loading reduced significantly, the AgPt NCs/C catalysts still showed the mass activity of 175.25 mA mg Metal -1 and specific activity of 0.35 mA cm -2 , which was better than those of the C-supported Pt (NPs) catalyst (161.02 mA mg Metal -1 for mass activity and 0.23 mA cm -2 for a specific activity), as depicted in Please do not adjust margins Please do not adjust margins Figure 6b and Table S3. The high catalytic activity of the AgPt NCs/C catalyst could be interpreted due to (i) the unique coral-like dendritic nanostructure of AgPt NCs, which supply more active sites and smooth routes for rapid diffusion and transfer of the reactants and products, promoting the oxidation process of small organic molecules; 47,48 (ii) the incorporation of Ag into Pt catalyst, boosting the activation of the surface-active sites of the Pt. The LSV test was performed to further record the electrocatalytic activity of the as-obtained AgPt NCs/C catalyst.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the Pt loading reduced significantly, the AgPt NCs/C catalysts still showed the mass activity of 175.25 mA mg Metal -1 and specific activity of 0.35 mA cm -2 , which was better than those of the C-supported Pt (NPs) catalyst (161.02 mA mg Metal -1 for mass activity and 0.23 mA cm -2 for a specific activity), as depicted in Please do not adjust margins Please do not adjust margins Figure 6b and Table S3. The high catalytic activity of the AgPt NCs/C catalyst could be interpreted due to (i) the unique coral-like dendritic nanostructure of AgPt NCs, which supply more active sites and smooth routes for rapid diffusion and transfer of the reactants and products, promoting the oxidation process of small organic molecules; 47,48 (ii) the incorporation of Ag into Pt catalyst, boosting the activation of the surface-active sites of the Pt. The LSV test was performed to further record the electrocatalytic activity of the as-obtained AgPt NCs/C catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…6b and Table S3 (ESI †). The high catalytic activity of the AgPt NCs/C catalyst could be interpreted as due to (i) the unique coral-like dendritic nanostructure of the AgPt NCs, which supplies more active sites and smooth routes for rapid diffusion and transfer of the reactants and products, promoting the oxidation process of small organic molecules; 47,48 (ii) the incorporation of Ag into the Pt catalyst, which enhanced the activation of the surfaceactive sites of the Pt. 4,49 The LSV test was performed to further record the electrocatalytic activity of the as-obtained AgPt NCs/C catalyst.…”
Section: Materials Advances Papermentioning
confidence: 99%
“…99 Addition of Co able to promote C C bond cleavage and facilitate adsorbed intermediates removal from the alloy surface 100 while providing oxophilicity induction to improve material electrocatalytic properties and electronic structure alteration for better catalytic performance and durability. 101 Jiang et al 102 and Sun et al 103 investigated multiple Pt/Co combination ratios towards GOR. Jiang et al 102 reported that at optimum molar ratio value, higher Pt content, the onset potential was more negative with the most increased mass activity and specific activity than others.…”
Section: Development Of Pt-based and Pdbased Catalyst With Cobalt Metalmentioning
confidence: 99%
“…101 Jiang et al 102 and Sun et al 103 investigated multiple Pt/Co combination ratios towards GOR. Jiang et al 102 reported that at optimum molar ratio value, higher Pt content, the onset potential was more negative with the most increased mass activity and specific activity than others. The dendritic structures provided high exposed active sites owing to the sufficient surface defects existence.…”
Section: Development Of Pt-based and Pdbased Catalyst With Cobalt Metalmentioning
confidence: 99%
“…Allantoin is a green nitrogen-rich heterocyclic compound derived from purine catabolism (Figure S1). 19 Its carbonyland amino-groups endow it possibility as the reductant and stabilizing agent, 20 as well as a good chelating agent with the metal precursors to decrease the reduction kinetics. 21 Herein, a facile solvothermal strategy was utilized to fabricate PtCu dodecahedral nanoframes (PtCu DNFs) in the presence of cetyltrimethylammonium chloride (CTAC), allantoin, and oleylamine (OAm).…”
Section: ■ Introductionmentioning
confidence: 99%